Left Colon Diverticulitis Presenting as Perforated Lumbar Abscess: A Case Report and Review of the Current Literature - Daniel Paramythiotis; Konstantinia Kofina; Vassileios N. Papadopoulos; Antonios Michalopoulos (Case Reports in Gastrointestinal Medicine)
Diverticular perforation is a common complication of diverticulitis and can lead to the creation of abscesses. The presence of such abscesses on the abdominal wall is rare and can lead to misdiagnosis. We present the case of a patient with abdominal pain and the formation of a large left lumbar abscess due to perforation of a diverticulum of the left colon and our surgical treatment of choice with favorable results.